2010
DOI: 10.1519/jsc.0b013e3181dc47f8
|View full text |Cite
|
Sign up to set email alerts
|

Postactivation Potentiation Following Different Modes of Exercise

Abstract: Usage of any items from the University of Cumbria's institutional repository 'Insight' must conform to the following fair usage guidelines.Any item and its associated metadata held in the University of Cumbria's institutional repository Insight (unless stated otherwise on the metadata record) may be copied, displayed or performed, and stored in line with the JISC fair dealing guidelines (available here) for educational and not-for-profit activities provided that• the authors, title and full bibliographic detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
3
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 22 publications
3
60
3
10
Order By: Relevance
“…In the present study, VCMJ performance increased after resistance exercise, similar to the results of other investigations that demonstrated a positive change in jumping performance after highintensity squat exercises 13,15 . Although the leg press is a multi-joint exercise (similar to jumping), biomechanically the two have some differences (e.g., the ballistic nature of jumping, and the different body positions) that could influence the post-activation potentiation response 16 .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, VCMJ performance increased after resistance exercise, similar to the results of other investigations that demonstrated a positive change in jumping performance after highintensity squat exercises 13,15 . Although the leg press is a multi-joint exercise (similar to jumping), biomechanically the two have some differences (e.g., the ballistic nature of jumping, and the different body positions) that could influence the post-activation potentiation response 16 .…”
Section: Discussionsupporting
confidence: 92%
“…Most studies found in the current review suggest the presence of post-activation potentiation in different athletics events 16,34,35,36,37,38,39 . This may be associated with neuromuscular and molecular changes induced by strength and power activities such as: 1) better recruitment of motor units, especially type-IIx motor units, which have a higher contraction velocity and capacity to generate tension; 2) increased availability of Ca ++ for contraction and 3) increased phosphorylation of light myosin chains, facilitating the interaction of contractile filaments 1,3 .…”
Section: Discussionmentioning
confidence: 78%
“…Karampatsos et al found greater distance in hammer throw one minute after three countermovement jumps (Pre = 62.92 ± 4.43 m, Post 64.42 ± 5.13 m, p = 0.047) and one minute after 20-m sprint (Pre = 64.87 ± 3.90 m, post = 65.30 ± 4.02 m, p = 0.013) in six experienced male hammer throwers. However, Esformes et al 38 analyzed the effects of 24 plyometric jumps with alternating legs on the height of counter movement jump (CMJ) in well-trained adult jumpers and sprinters and found no difference in CMJ after five minutes of interval between conditioning activities (p> 0.05). According to the author, the duration of jumps used in the study was too long, which required less intensity for its accomplishment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it can also enhance subsequent force generation and improve strength and power performance (3,8,11,16,21,23), a phenomenon termed post-activation potentiation (PAP). PAP has been attributed to three possible mechanisms; regulatory light chains phosphorylation, increased recruitment of motor units, and muscle fibre pennation angle change (for review see 22).…”
Section: Introductionmentioning
confidence: 99%